Isolation of the beta-hemolytic streptococcus in asymptomatic children - Neysi Soria Barreda; Mayda Guilart Domínguez; Ceres Guerrero Pardo; María Caridad Mariño Castellanos (Centro Provincial de Información de Ciencias Médicas, 2017)
Introduction: pharyngotonsillitis is among the infectious diseases that most affect children in school age whose first bacterial cause is the group A beta-hemolytic streptococcus. Objective: to be determine the presence of this bacteria in throat swabs of asymptomatic children. Methods: a cross-sectional and descriptive study of 80 children from both sexes was carried out in "Alberto Fernández" day care center in Santiago de Cuba, during 2014. Results: a high percentage of infected children by potentially pathogens bacterias was obtained, with prevalence of group A beta-hemolytic streptococcus, as well as a higher frequency of children of the male sex aged 4 and 5; also, the antibiotics of more sensitivity were penicillin and amoxicillin, while kanamycin was that of higher resistance. Conclusions: with this investigation the colonization characteristics of this bacteria were known, as well as its antimicrobian sensitivity.